Time scales of erosion and deposition recorded in the residual south polar cap of Mars - Thomas, P.C.; Calvin, W.M.; Gierasch, P.; Haberle, R.; James, P.B.; Sholes, S. (Icarus (New York, N.Y. 1962), 2013)
► The residual south polar cap of Mars fluctuates in area yet is eroding within its cover of CO2 ice. ► Different morphologic units in the cap have different rates of scarp retreat. ► The oldest units suggest both deposition and erosion over more than 100 Mars years. ► Thinner units show changing erosional periods of Mars decades. The residual south polar cap (RSPC) of Mars has been subject to competing processes during recent Mars years of high resolution image coverage: continuing erosion of scarps while the maximum extent grows as well as shrinks (Piqueux, S., Christensen, P.R. [2008]. J. Geophys. Res. (Planets) 113, 2006; James, P.B., Thomas, P.C., Malin, M.C. [2010]. Icarus 208, 82–85). Additionally, the cap has a variety of morphologies and erosion (scarp retreat) rates (Thomas, P.C., James, P.B., Calvin, W.M., Haberle, R., Malin, M.C. [2009]. Icarus 203, 352–375). Do these different forms and competing processes indicate an aging and possibly disappearing cap, a growing cap, or a fluctuating cap, and is it possible to infer the timescales of the processes acting on the RSPC? Here we use the latest imaging data from Mars’ southern summer in Mars year 30 (Calendar year 2011) to evaluate erosion rates of forms in the RSPC over 6Mars years, and to map more fully features whose sizes can be used to predict deposit ages. Data through Mars year 30 show that scarp retreat rates in the RSPC have remained approximately the same for at least 6Mars years and that these rates of erosion also apply approximately over the past 21Mars years. The thicker units appear to have undergone changes in the locations of new pit formation about 30–50Mars years ago. The thinner units have some areas that are possibly 80Mars years old, with some younger materials having accumulated more than a meter in thickness since Mars year 9. Formation of the thicker units probably required over 100Mars years. The upper surfaces of most areas, especially the thicker units, show little change at the few-cm level over the last 2Mars years. This observation suggests that current conditions are substantially different from those when the thicker units were deposited. A prime characteristic of the evolution of the RSPC is that some changes are progressive, such as those involving scarp retreat, while others, such as the geography of initiation of new pits or the areal coverage of ice, appear to be more episodic.